Suku Anak Dalam di Desa Sungai Abang: Perubahan dalam Bidang Pendidikan, Kepercayaan, dan Teknologi (2010–2024) - Savitri, Wahyuni; Salam, Abdul (Lembaga Yasin AlSys, 2025)
The Suku Anak Dalam (SAD) is an indigenous community historically reliant on forests and characterized by a semi-nomadic lifestyle, but in recent decades has undergone significant changes due to intensive interaction with external society, government policies, and the penetration of modern values. This study aims to describe the transformations in the lives of the SAD in Sungai Abang Village, VII Koto Subdistrict, Tebo Regency, Jambi Province, particularly in the areas of education, belief systems, and technology during the period 2010–2024. The method used is historical research with a qualitative approach, encompassing the stages of heuristics, source criticism, interpretation, and historiography. The research focuses on the Bujang Rimbo group, which has settled permanently and demonstrates more complex social dynamics compared to nomadic groups. Data were collected through in-depth interviews, field observations, and documentation studies, and analyzed thematically. The findings reveal increased access to formal education, religious acculturation through the adoption of formal religions such as Islam, and the use of communication technology that has altered social interaction patterns within the community. In conclusion, the SAD’s adaptation to social change occurs gradually, selectively, and contextually, reflecting the community's ability to maintain cultural identity while responding to the challenges and opportunities of modernity. These findings contribute to a deeper understanding of how indigenous communities navigate contemporary social transformation.